A CHARACTER-BASED ASSESSMENT MODEL FOR VOCATIONAL HIGH SCHOOLS - Edy Supriyadi; Zamtinah Zamtinah; Sunaryo Soenarto; Yuwono Indro Hatmojo (LPMPP Universitas Negeri Yogyakarta, 2019)
The competencies of vocational high school (VHS) graduates, especially in terms of character have not met its standards. This study aims to develop a character-based assessment model for VHS in the form of a guide and procedure. Borg Gall’s (1989) model with the following stages was utilized: (1) needs analysis, (2) planning, (3) development, (4) phase I trial, (5) phase II trial, (6) evaluation of model effectiveness, and (7) final product development. This study involved some experts in the model validation. Trials were done to teachers and principals in eight VHSs in Yogyakarta Special Province, Indonesia in 2017 (first trial), and those from 42 VHSs throughout Java island, Indonesia in 2018 (second trial). Data were collected by questionnaires and interviews and analysed by quantitative and qualitative descriptive statistics. This study suggest that, overall, the model is appropriate and feasible to use, proven by (1) the assessment guide is categorized as ‘very appropriate’ (Mean 3.55; SD .52); (2) assessment procedure achieves an ‘very appropriate’ category (Mean = 3.60; SD = .51); and (3) effectiveness of the assessment model in trial 1 is in the ‘very appropriate’ category (Mean 3.43, and SD .51), and in trial 2 is in the ‘appropriate’ category (Mean 3.38, SD .53).